Control and evaluation of information resources from a "continent" curation approach - Urbano, Cristóbal (Anuario ThinkEPI, 2016)
This article reflects on the need to re-interpret the control and evaluation of information resources in the current environment of online searching and the information domination of search engines and social networks. Taking into account the recent announcement of the ending of ALA´s Guide to reference, and considering the years before the disappearance of selective directories of web resources like Intute, we attempt to explore the potential of content curation as a conceptual and methodological approach to control and evaluate quality information resources. These resources can be viewed as "continents" with a clear and planned identity where the "contents" experience a kind of dissolution within search engines and social networks. This article proposes the concept of "continent curation" as a method of valuation and contextualization for reference resources within the realm of library and information literacy work.